Transcranial high intensity focused ultrasound therapy guided by 7 TESLA MRI in a rat brain tumour model: A feasibility study. (September 2013) - Dervishi, Elvis; Larrat, Benoit; Pernot, Mathieu; Adam, Clovis; Marie, Yannick; Fink, Mathias; Delattre, Jean-Yves; Boch, Ann-Laure; Tanter, Mickael; Aubry, Jean-Francois
Abstract Purpose: Transcranial high intensity focused ultrasound (HIFU) therapy guided by magnetic resonance imaging (MRI) is a promising approach for the treatment of brain tumours. Our objective is to validate a dedicated therapy monitoring system for rodents for transcranial HIFU therapy under MRI guidance in an in vivo brain tumour model. Materials and methods: A dedicated MR-compatible ultrasound therapy system and positioning frame was developed. Three MR-compatible prefocused ultrasonic monoelement transducers were designed, operating at 1.5 MHz and 2.5 MHz with different geometries. A full protocol of transcranial HIFU brain therapy under MRI guidance was applied in n = 19 rats without and n = 6 rats with transplanted tumours (RG2). Different heating strategies were tested. After treatment, histological study of the brain was performed in order to confirm thermal lesions. Results: Relying on a larger aperture and a higher frequency, the 2.5 MHz transducer was found to give better results than other ones. This single element transducer optimised the ratio of the temperature elevation at the focus to the one at the skull surface. Using optimised transducer and heating strategies enabled thermal necrosis both in normal and tumour tissues as verified by histology while limiting overheating in the tissues in contact with the skull. Conclusions: In this study, a system for transcranial HIFU therapy guided by MRI was developed and tested in an in vivo rat brain tumour model. The feasibility of this therapy set-up to induce thermal lesions within brain tumours was demonstrated.